2024
DOI: 10.1038/s41598-024-53110-3
|View full text |Cite
|
Sign up to set email alerts
|

Preverbal infants’ understanding of social norms

Moritz Köster,
Robert Hepach

Abstract: Social norms are foundational to human cooperation and co-existence in social groups. A crucial marker of social norms is that a behavior is not only shared, but that the conformity to the behavior of others is a basis for social evaluation (i.e., reinforcement and sanctioning), taking the is, how individuals usually behave, to an ought, how individuals should behave to be socially approved by others. In this preregistered study, we show that 11-month-old infants grasp this fundamental aspect about social norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Cognitively, it has been shown that from around this age, infants associate imitative behaviors with group membership and, from around 8 months, infants further expect that the members of a group act alike (Powell and Spelke, 2013 , 2018 ). Furthermore, there is recent evidence that already 11-month-olds grasp the normative force of behavior observed in others and that behaving like others forms the basis for social evaluation (Köster and Hepach, 2024 ). So how are these prerequisites for early social learning, as the basis for cultural learning and normativity, shaped in social interaction with others?…”
Section: A Lifeworld Approach To Social- Cognitive Developmentmentioning
confidence: 99%
“…Cognitively, it has been shown that from around this age, infants associate imitative behaviors with group membership and, from around 8 months, infants further expect that the members of a group act alike (Powell and Spelke, 2013 , 2018 ). Furthermore, there is recent evidence that already 11-month-olds grasp the normative force of behavior observed in others and that behaving like others forms the basis for social evaluation (Köster and Hepach, 2024 ). So how are these prerequisites for early social learning, as the basis for cultural learning and normativity, shaped in social interaction with others?…”
Section: A Lifeworld Approach To Social- Cognitive Developmentmentioning
confidence: 99%